MANAJEMEN METADATA ARSIP AUDIO DENGAN APLIKASI SEDERHANA PERKANTORAN PADA MUSEUM MUSIK INDONESIA - Anastasya, Diva; Mihasu, Narocha; Cornellya, Safira; Nikmah, Farika (Dharma: Jurnal Pengabdian Masyarakat, 2023)
Metadata provides the necessary context to understand and organize systems, data, and content management. Thus the metadata in the archive has a fairly important role, with the existence of archive metadata it will facilitate the management of archives, both static archives or dynamic archives. At the Indonesian Music Museum in Malang City, there are various collections of audio archives from all over Indonesia which are static archives that need to be preserved for their authenticity and physicality as they are part of Indonesia's cultural heritage. The archive collection is divided into various forms, namely in the form of tape cassettes, CDs, and LPs. This study aims to describe the needs of metadata management within the scope of electronic records management. Metadata management is compiled by recording a collection of audio archives on tape cassettes for the pop song category at the Indonesian Music Museum. The metadata management development approach uses a simple office application with Microsoft Access media, so that the audio archive metadata in the Indonesian Music Museum can be digitally compiled. Of course, this can facilitate audio archive retrieval activities and their maintenance.